Still : notes on a mid-faith crisis - Winner, Lauren F. (New York : HarperOne, 2012)
Shares the author's experience of finding faith during her times of doubt and crisis when her marriage unraveled, and describes how she overcame her "middle stage" of her spiritual life to find hope and healing.
Includes bibliographical references.
Keywords: Winner, Lauren F; Christian life -- Anglican authors; Anglican converts -- United States -- Biography